Vonoprazan and high‐dose amoxicillin dual therapy for Helicobacter pylori first‐line eradication: A single‐arm, interventional study. Issue 1 (8th December 2022) - Sue, Soichiro; Kondo, Masaaki; Sato, Takeshi; Oka, Hiroyuki; Sanga, Katsuyuki; Ogashiwa, Tsuyoshi; Matsubayashi, Mao; Kaneko, Hiroaki; Irie, Kuniyasu; Maeda, Shin
Abstract: Background: To date, no interventional trial has assessed the efficacy and safety of vonoprazan and high‐dose (500 mg four times daily, 2000 mg/day) amoxicillin dual therapy in terms of Helicobacter pylori eradication. We explored whether this was an appropriate first‐line treatment. Methods: This prospective, dual‐center, single‐arm interventional study was performed in Japan. Twenty H. pylori ‐positive patients lacking any eradication history were treated with vonoprazan 20 mg twice daily and amoxicillin 500 mg four times daily (qid) for 7 days. Eradication was evaluated using a stool H. pylori antigen test. We evaluated safety using patient questionnaires. This study was registered in the jRCT database (jRCT031200128). Results: The intention‐to‐treat and per‐protocol eradication rates were 90% (95% confidence interval [CI] 68.3–98.8%, n  = 20) and 94.4% (95% CI 72.7–99.9%, n  = 18) respectively. No significant adverse event was recorded. Conclusion: Vonoprazan/high‐dose amoxicillin dual therapy can be a safe standard first‐line therapy. We are now undergoing a randomized controlled trial comparing dual therapy and vonoprazan‐based triple therapy. Abstract : This interventional study showed the efficacy of Vonoprazan/high‐dose (500 mg four times daily) amoxicillin dual therapy. No significant adverse event was recorded.